Surgical wound care preferences and priorities from the perspectives of patients: a qualitative analysis. (2nd January 2023) - Walker, Rachel M; Rattray, Megan; Lockwood, Ishtar; Chaboyer, Wendy; Lin, France; Roberts, Shelley; Perry, Jodie; Birgan, Sean; Nieuwenhoven, Paul; Garrahy, Elizabeth; Probert, Rosalind; Gillespie, Brigid M
Abstract : Objective: To explore patients' priorities and preferences for optimal care of their acute or hard-to-heal surgical wound(s). Method: This qualitative study involved semi-structured individual interviews with patients receiving wound care in Queensland, Australia. Convenience and snowball sampling were used to recruit patients from inpatient and outpatient settings between November 2019 and January 2020. Interviews were audio recorded, transcribed verbatim and analysed using thematic analysis. Emergent themes were discussed by all investigators to ensure consensus. Results: A total of eight patients were interviewed, five of whom were male (average median age: 70.5 years; interquartile range (IQR): 45–80 years). Four interrelated themes emerged from the data that describe the patients' surgical wound journey: experiencing psychological and psychosocial challenges; taking back control by actively engaging in care; seeking out essential clinician attributes; and collaborating with clinicians to enable an individualised approach to their wound care. Conclusion: Findings from this study indicate that patients want to actively collaborate with clinicians who have caring qualities, professional skills and knowledge, and be involved in decision-making to ensure care meets their individual needs.